Energy Efficient Precoder Design for Non-Regenerative MIMO-CRN - Maurya, Shikha; Bansal, Matadeen (IEEE wireless communications letters, 2017)
This letter presents a problem of designing a relay precoding matrix for a multi-input multi-output cognitive relay network, where a secondary system (SS) works in an underlay mode and communicates through a non-regenerative relay. An optimization problem is formulated to maximize the energy efficiency of the SS subject to a transmit power constraint and an interference constraint. An efficient scheme based on the fractional programming and augmented Lagrangian multiplier method is proposed to solve the resultant problem. Numerical results are provided to show the effectiveness of the proposed scheme.